KEBUTUHAN PEMBACAAN BARU DI TENGAH MASYARAKAT MULTIKULTURAL - Fauzan Azhima (NIHAYAH: Journal of Islamic Studies, 2025)
This article explores the urgency of renewing interpretive methodologies of religious texts within today’s multicultural society. By observing religious practices in three culturally and religiously diverse communities, this study integrates contextual hermeneutics with socio-historical analysis. The findings reveal varying community responses to alternative readings rooted in local wisdom and the objectives of Islamic law (maqāṣid al-sharī‘ah). On one hand, such approaches bridge the gap between scripture and contemporary realities; on the other, they provoke resistance among traditionalists concerned with the risks of relativism. Contextual interpretation serves not only as an epistemological bridge between religious values and cultural diversity, but also as a gateway to more inclusive religious practices. The article emphasizes the need for collaborative strategies among scholars, religious leaders, and policymakers to enhance interpretive literacy and strengthen adaptive religious ethics. Methodological reform is thus not merely an academic issue but a strategic measure to maintain social cohesion amid globalization. Consequently, reinterpreting sacred texts through a contextual lens offers a balanced pathway that preserves tradition while ensuring contemporary relevance.